The complex pathophysiology of bone fragility in obesity and type 2 diabetes mellitus: therapeutic targets to promote osteogenesis - Bathina, Siresha; Armamento-Villareal, Reina (Frontiers in Endocrinology, 2023)
Fractures associated with Type2 diabetes (T2DM) are major public health concerns in an increasingly obese and aging population. Patients with obesity or T2DM have normal or better than normal bone mineral density but at an increased risk for fractures. Hence it is crucial to understand the pathophysiology and mechanism of how T2DM and obesity result in altered bone physiology leading to increased fracture risk. Although enhanced osteoclast mediated bone resorption has been reported for these patients, the most notable observation among patients with T2DM is the reduction in bone formation from mostly dysfunction in osteoblast differentiation and survival. Studies have shown that obesity and T2DM are associated with increased adipogenesis which is most likely at the expense of reduced osteogenesis and myogenesis considering that adipocytes, osteoblasts, and myoblasts originate from the same progenitor cells. Furthermore, emerging data point to an inter-relationship between bone and metabolic homeostasis suggesting that these physiologic processes could be under the control of common regulatory pathways. Thus, this review aims to explore the complex mechanisms involved in lineage differentiation and their effect on bone pathophysiology in patients with obesity and T2DM along with an examination of potential novel pharmacological targets or a re-evaluation of existing drugs to improve bone homeostasis.